Participant perceptions of residential learning. - Jean Anderson Fleming (Adult Education Research Conference, 1997)
This paper reviews findings from a study of participant perceptions of residential adult learning. Residential learning programs were defined as programs in which participants live and learn together, full-time, in the same location, for the full duration of their program.